2012
DOI: 10.1186/1756-6614-5-13
|View full text |Cite
|
Sign up to set email alerts
|

Elevated thyroid stimulating hormone is associated with elevated cortisol in healthy young men and women

Abstract: BackgroundRecent attention has been given to subclinical hypothyroidism, defined as an elevation of TSH (4.5-10 uIU/L) with T4 and T3 levels still within the normal range. Controversy exists about the proper lower limit of TSH that defines patients in the subclinical hypothyroidism range and about if/when subclinical hypothyroidism should be treated. Additional data are needed to examine the relationship between markers of thyroid function in the subclinical hypothyroidism range, biomarkers of health and ultim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 24 publications
4
29
0
Order By: Relevance
“…No correlation was found between cortisol and FT4 levels, which is consistent with previously reported data in the specialized literature (30).…”
Section: Discussionsupporting
confidence: 93%
“…No correlation was found between cortisol and FT4 levels, which is consistent with previously reported data in the specialized literature (30).…”
Section: Discussionsupporting
confidence: 93%
“…Thyroid hormone analysis in the present case-control study revealed significantly higher mean TSH level of the SCH group as compared to the euthyroid group, in contrast to the results of the comparison of free T3 and T4 levels, between the groups. In addition, the free T3 and T4 levels between the groups in the present study were similar, consistent and within the normal range, similar to the observation by Walter et al (13) . In the present study, the mean values of serum cholesterol, triglycerides and apolipoprotein A was significantly high in the SCH group.…”
Section: Resultssupporting
confidence: 80%
“…Elevated levels of cortisol due to stress have observed to interfere with thyroid function in fish Walpita et al (2007). Chronic elevation in cortisol negatively feeds back the hypothalamus-pituitary-interrenal axis thus decreasing the peripheral circulating levels of T4 and T3 (Walter et al, 2012). Furthermore, prolonged cortisol elevations, caused by chronic stress, decrease the liver's ability to clear excess estrogens from the blood (Santin and Furlanetto, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In Amur sturgeon (Acipenser schrenckii), serum concentrations of total triiodothyronine (T3), free T4, and free T3 have been found inversely related to higher stocking densities, whereas serum total T4 level remained stable Li et al (2012). Crowding stress-induced elevation in levels of cortisol while suppression in profile of T4 might be due to negative feedback mechanism of elevated cortisol level on hypothalamus-pituitary-interrenal axis thus decreasing (Walter et al, 2012). Insufficient levels of circulating T4 levels and their carrier proteins (Fazio, Faggio, Piccione, Bonfiglio, & Marino, 2014) may cause the suppression of fish growth as observed in brook charr (Salvelinus fontinalis) (Vijayan, Ballantyne, & Leatherland, 1988).…”
Section: Introductionmentioning
confidence: 99%